Search for bose glass phase in the Shastry-Sutherland model - Leong, Wui Seng (2014)
Physicists are interested on the physical properties during the phase transition of lattices under various Hamiltonian model. In this project, we are dealing with the hard core boson in the Shastry-Sutherland model under the Bose-Hubbard Hamiltonian model, where the diagonal bonds and square (vertical and horizontal) bonds are of different strength. We only focus on the low temperature since we want to search its Bose glass phase. In this project, 4 physical properties are determined: boson density, structure factor, stiffness and energy, by using the one of the quantum Monte Carlo methods called the stochastic series expansion.